Co-creation of a Scalable Climate Service for Kenyan Smallholder Farmers - van der Horst, Sophie; Goosen, Hasse; van Selm, Merlijn; Koomen, Irene; Matsaba, Emmanuel Ochola; Wesonga, John; Koge, Jessica; klein Holkenborg, Marjel (Frontiers in Climate, 2022)
Climate change is already impacting the horticulture sector in Kenya. Even though the effects of climate change will be severe, adaptation to climate change still has little priority at the local and county level. This paper discusses the development of the agricultural climate atlas for Kajiado and Kiambu counties in Kenya as a climate information service to support the horticulture sector. This climate service for smallholder farmers aims to bridge the gap between climate research and data provision and the uptake by farmers and farmer organizations on the ground. Rather than developing a generic service for the whole of the country, we followed a local, bottom-up approach. Working at the county level, we tried to capture local needs. The result is a co-created atlas for two counties, for specific crops. The approach can be scaled up to other counties and other crops. We elaborate on our approach, and discuss lessons learned, challenges, and future work opportunities. The development of the climate atlas shows the importance of co-creation and user engagement. In addition, flexibility in the output and process was crucial. The main challenge remains to keep engagement high after completion of the project.